A spatial re-consideration of the early childhood-school relationship. Issue 6 (17th August 2016) - Henderson, Linda; Nuttall, Joce; Kriegler, Lili-Ann; Schiele, Helen
Abstract: This paper undertakes a spatial examination of the early childhood–school relational space. It theorizes space as a product of interrelationships, moving therefore beyond an understanding of space as fixed and horizontal. Drawing on data from a pilot project with early childhood and junior primary teachers working in an independent (i.e. private, fee-paying) school, the experience of meeting across the early childhood–school divide is examined. We ask how space is produced and what types of relationships emerge in its production. The paper concludes by arguing that the production of open and dynamic spatial arrangements is key to creating new ways of being in relationship across the early childhood–school divide.